Implementation of the Open Defecation Free (ODF) Pillar of Community-Led Total Sanitation (CLTS) Program in East Kalimantan, Indonesia - Suryanti, Ratna (Jurnal KESANS : Kesehatan dan Sains, 2025)
The implementation of the first pillar of the Community-Based Total Sanitation (CLTS) program, targeting the elimination of Open Defecation (OD), has yielded varying outcomes across regions, including East Kalimantan. Program success is closely linked to factors such as community knowledge, local culture, access to sanitation infrastructure, and the involvement of health workers and local leaders. Approaches like Community-Led Total Sanitation (CLTS) and Ecological Sanitation (EcoSan) demonstrate different levels of effectiveness depending on geographic conditions and institutional support. In East Kalimantan, challenges such as dispersed settlements, limited access to clean water, and substandard housing quality hinder program outcomes. Nevertheless, programs integrating education, appropriate technology, community participation, and adaptive policies have proven to reduce diarrhea incidence, lower stunting rates, and raise sanitation awareness. Cross-sectoral collaborative strategies are essential to achieving sustainable and context-sensitive sanitation behavior change in this region.